Ethanol marshall bundle elimination, pulmonary vein isolation, and linear ablation for atrial fibrillation with or without heart failure - Chen, Hongxu; Li, Huahua; Chen, Dan; Xiong, Xiong; Li, Xi; Chen, Yanhong; Zhang, Jinlin (Frontiers in Cardiovascular Medicine, 2024)
BackgroundIn medical practice, atrial fibrillation (AF) is intricately associated with heart failure (HF). Currently, ethanol infusion of vein of Marshall (EIVOM) for AF ablation in HF patients remains significantly limited.MethodThis was a non-randomized, single-center, retrospective observational study. AF patients received 4-step ablation composed of EIVOM, pulmonary vein isolation (PVI) and linear ablation. The primary composite endpoint was defined as recurrence of atrial tachycardia over 30 s. Propensity score matching (PSM) was performed to reduce selection bias.ResultsFrom April 2020 to May 2022, 362 patients were included, comprising of 182 HF patients and 180 non-HF patients. EIVOM success rate was lower in HF patients than non-HF patients (86.8% vs. 93.9%). Cardiac effusion was more common in HF patients (44.0% vs. 37.2%), and 2 cases of atrial-esophageal fistula were observed in the HF group. During a median follow-up of 12 months, no significant difference in the primary endpoint was observed between HF and non-HF group. Different HF subgroups had similar AF recurrence. After PSM, AF recurrence rate remained statistically equivalent between the HF and non-HF groups.ConclusionEVIOM combining catheter ablation can be completed with comparable success rate in AF patients with or without HF. However, peri-procedural safety is a concern for HF patients undergoing EIVOM combing AF catheter ablation. During the follow-up, HF status before ablation is not related with increased AF recurrence.